Biomechanical Comparison of the Latarjet Procedure with and without Capsular Repair - Kleiner, Matthew T. (Clin Orthop Surg, 2016)
BACKGROUND: The purpose of this study was to determine if capsular repair used in conjunction with the Latarjet procedure results in significant alterations in glenohumeral rotational range of motion and translation. METHODS: Glenohumeral rotational range of motion and translation were measured in eight cadaveric shoulders in 90° of abduction in both the scapular and coronal planes under the following four conditions: intact glenoid, 20% bony Bankart lesion, modified Latarjet without capsular repair, and modified Latarjet with capsular repair. RESULTS: Creation of a 20% bony Bankart lesion led to significant increases in anterior and inferior glenohumeral translation and rotational range of motion (p < 0.005). The Latarjet procedure restored anterior and inferior stability compared to the bony Bankart condition. It also led to significant increases in glenohumeral internal and external rotational range of motion relative to both the intact and bony Bankart conditions (p < 0.05). The capsular repair from the coracoacromial ligament stump to the native capsule did not significantly affect translations relative to the Latarjet condition; however it did cause a significant decrease in external rotation in both the scapular and coronal planes (p < 0.005). CONCLUSIONS: The Latarjet procedure is effective in restoring anteroinferior glenohumeral stability. The addition of a capsular repair does not result in significant added stability; however, it does appear to have the effect of restricting glenohumeral external rotational range of motion relative to the Latarjet procedure performed without capsular repair.